Tungsten filament fire. (16th March 2016) - Ruiz, Michael J; Perkins, James
Abstract: We safely remove the outer glass bulb from an incandescent lamp and burn up the tungsten filament after the glass is removed. This demonstration dramatically illustrates the necessity of a vacuum or inert gas for the environment surrounding the tungsten filament inside the bulb. Our approach has added historical importance since the incandescent light bulb is being replaced by compact fluorescent and LED lamps.